PHYTOCHEMICAL CONSTITUENTS AND ANTIOXIDANT EFFECT OF SOLANUM ROSTRATUM SPECIES FROM ALGERIA T - Omar, Tebboub; Noman, Labib; Mohamed, Bouhroume; Oke Altuntas, Feyza; Demirtas, Ibrahim (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to isolate the constituents and evaluate the antioxidant activity of Solanum rostratum Dunal (Solanaceae) from Algeria. Methods: In this study, phytochemical analyses of the chloroform, ethyl acetate, and n-butanol extracts obtained from the aerial parts of S. rostratum were performed by column chromatography, thin-layer chromatography, and high-performance liquid chromatography techniques. The antioxidant activity was performed by 2,2-diphenyl-1-picrylhydrazyl scavenging assay method. Results: The identification and structure elucidation of the isolated compounds were compared with their nuclear magnetic resonance spectra and the literature led to identify one monoterpene glycoside (linalyl-Î²-glucopyranoside) (1) and three flavonoid glycosides: Apigenin-7-O-glucoside (2), astragalin (3) and (isorhamnetin-3-O-glucoside (4). Conclusion: This is the first report on the isolation and structure elucidation of compound (1) (linalyl-Î²-glucopyranoside) and compound (2) (apigenin-7-O-glucoside) from this species. In addition, antioxidant effect of the chloroform extract from S. rostratum was evaluated. The chloroform extract exhibited the remarkable radical scavenging ability (IC50=0066Â±0.001 mg/mL).